An autopsy case of bird-related chronic hypersensitivity pneumonitis presenting with repeated acute exacerbation. (2018) - Mikumo, Hironori; Yanagihara, Toyoshi; Hamada, Naoki; Hashisako, Mikiko; Ijichi, Kayo; Suzuki, Kunihiro; Harada, Eiji; Shikada, Yasunori; Oda, Yoshinao; Nakanishi, Yoichi
Abstract: A 68-year-old woman was admitted to our hospital with a dry cough in 2010. Chest computed tomography showed the appearance of a nonspecific interstitial pneumonia (NSIP) pattern. Video-assisted thoracoscopic surgery (VATS) was performed, and the specimens prominently showed a usual interstitial pneumonia (UIP) pattern. She was diagnosed with bird-related chronic hypersensitivity pneumonitis (BRCHP) on the basis of the detection of antibodies to pigeon dropping extract in her serum and a history of using feather-filled duvets and indirect exposure to birds in her living environment. Even though she was treated with corticosteroids and immunosuppressants and recommended to avoid bird-related antigens, she had a progressive course with repeated acute exacerbation episodes and died of respiratory failure. The autopsy findings showed diffuse alveolar damage superimposed on UIP. Clinicians should be aware that BRCHP patients especially with histopathologically UIP pattern may experience acute exacerbation.